2015
DOI: 10.1111/febs.13210
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the broad substrate specificity of carboxypeptidase T from Thermoactinomyces vulgaris

Abstract: The crystal structures of carboxypeptidase T (CpT) complexes with phenylalanine and arginine substrate analogs -benzylsuccinic acid and (2-guanidinoethylmercapto)succinic acid -were determined by the molecular replacement method at resolutions of 1.57 A and 1.62 A to clarify the broad substrate specificity profile of the enzyme. The conservative Leu211 and Leu254 residues (also present in both carboxypeptidase A and carboxypeptidase B) were shown to be structural determinants for recognition of hydrophobic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Meanwhile, the highly abundant no-rank Actinobacteria in JF liquor starter (J3 and J4) could produce volatile organic compounds; the secondary metabolic products of Actinomyces could also contribute to flavor development 38 . Thermoactinomyces can produce plenty of thermostable extracellular proteolytic enzymes, e.g., alkaline proteinase 39 , glutamyl endopeptidase 40 and carboxypeptidase 41 . This study further found that Bacillales and no-rank Actinobacteria were the dominant communities when the temperature increased to the highest point.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the highly abundant no-rank Actinobacteria in JF liquor starter (J3 and J4) could produce volatile organic compounds; the secondary metabolic products of Actinomyces could also contribute to flavor development 38 . Thermoactinomyces can produce plenty of thermostable extracellular proteolytic enzymes, e.g., alkaline proteinase 39 , glutamyl endopeptidase 40 and carboxypeptidase 41 . This study further found that Bacillales and no-rank Actinobacteria were the dominant communities when the temperature increased to the highest point.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic parameters of ZAAL, ZAAE and ZAAR hydrolysis by CPT were determined as described earlier [16].…”
Section: Methodsmentioning
confidence: 99%
“…Other factors important for an enzyme’s catalytic activity and substrate specificity can be related to the non-productive binding of a substrate or necessity to reposition the substrate in the course of its catalytic conversion in the active site of the enzyme. In CPT catalysis it has been shown, for example, that the side chain of the positively charged substrate should undergo repositioning when moving from the enzyme-substrate complex to the transition state, whereas the side chain of the hydrophobic substrate does not need repositioning [16]. However, it is not clear how different the structural organization of the transition complexes is at conversion of different substrates by CPT and what factors influence its substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in the insulin industry and in drug development as a model for blood carboxypeptidase B (Bunnage et al, 2007). We used carboxypeptidase B as a prototype to investigate the structural basis of the wide substrate selectivity of carboxypeptidase T from Thermoactinomyces vulgaris (Grishin et al, 2008;Akparov et al, 2015). Because these investigations were conducted for the rational design of metallocarboxypeptidase B with improved or changed selectivity, they required detailed information about the active site in order to provide a three-dimensional structure of the complex with the transition-state analogue of an arginine substrate.…”
Section: Introductionmentioning
confidence: 99%